A Study of New Normal Administration Components according to Good Governance of Schools under the Sakon Nakhon Primary Educational Service Area Office in Sakon Nakhon Province - Chumpunya, Ponchai; Phengsawat, Waro; Nanthasri, Wanphen (Dhammathas Academic Journal, 2023)
This research article aimed to study of New Normal Administration Components according to Good Governance of Schools under the Sakon Nakhon Primary Educational Service Area office in Sakon Nakhon Province. The informant group was academics, education executives, and school administrators, 10 people. Research tools were interview forms and questionnaires. Data were analyzed by content analysis, mean, and standard deviation. The results of the research: revealed that the administration components of the new according tothe principles of good governance of schools under the Office of Primary Educational Service Area in Sakon Nakhon Province, there are 8 components and 43 indicators namely 1) New normal Management Planning, there were 5 indicators, 2) New normal Working Methods, there were 5 indicators, 3) New normal Learning Curriculum Administration There were 5 indicators, 4) New normal Learning Management There were 5 indicators, 5) New normal Learning Evaluation Assessment, there were 7 indicators, 6) New normal Resource Management, there were 5 indicators, 7) New normal Cooperation, there were 6 indicators, and 8) Security, there were 5 indicators.